Strengthening community seed banks in East and Southern Africa in times of Covid-19 - Kimani, Dominic; Adokorach, Joyce; Munkombwe, Graybill; Mushita, Andrew; Otieno, Gloria Atieno; Recha, Tobias; Subedi, Abishkar; Vernooy, Ronnie (2021)
This brief presents the highlights of the work done in 2020 in East and Southern Africa – in the difficult context of the outbreak of Covid 19− to strengthen community seed banks and foster the collaboration between them and with the national genebank of each country. Highlights include the development of a protocol for the collaboration between a national genebank and community seed banks; seed and knowledge exchanges between the national genebank of Kenya and community seed banks; the development of a standard operational procedure for community seed banks in Uganda; the establishment of the first community seed bank under the ‘umbrella’ of the Zambia Agricultural Research Institute; and the exploration of opportunities for registration of farmer seed and supporting the formulation of enabling policies for smallholder farmer seed systems in Zimbabwe.